ANALISIS FAKTOR PENYEBAB KESULITAN MEMBACA PESERTA DIDIK KELAS TINGGI DI SEKOLAH DASAR NEGERI 1 LAMBHEU - Nurhayati; Intan Safiah; Suci Fitriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is entitled "Analysis of Factors Causing Reading Difficulties in Upper-Grade Students at SD Negeri 1 Lambheu". The purpose of this study is to describe the forms of reading difficulties experienced by upper-grade students, identify the causal factors, and describe the roles of teachers and parents in overcoming these issues. This research employs a qualitative approach with a descriptive research type. The research subjects consisted of three upper-grade students (grades IV, V, and VI) and three classroom teachers at SD Negeri 1 Lambheu. Data collection techniques were carried out through observation, interviews, and documentation. The results showed that the forms of reading difficulties experienced included difficulty understanding new vocabulary, difficulty reading long texts, and a lack of interest in reading materials with minimal illustrations. The main factors causing these difficulties are low concentration due to environmental distractions (such as gadgets and television), low learning motivation, as well as the lack of interesting reading materials at school and literacy support at home. In conclusion, reading difficulty in upper grades is a complex issue influenced by both internal and external factors, thus requiring strong synergy between the school and parents to address it